2012
DOI: 10.1017/s1049096511001764
|View full text |Cite
|
Sign up to set email alerts
|

Career Preparation and the Political Science Major: Evidence from Departments

Abstract: We know little about the amount of career preparation offered to students in political science departments. This lack of information is particularly troubling given the state of the current job market and the growth of applied degree programs on university campuses. To address this issue, this article presents the results of a December 2010 survey of 279 political science department chairs that asked questions about the level of career preparation in their respective departments. Based on our empirical finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…As Collins, Knotts, and Schiff (2012) have illustrated, this can be accomplished in many ways. They present 11 ideas, including adding to the curriculum required internship and career preparation courses and embedding elements of career preparation in other courses.…”
Section: Discussion: Enhancing Workplace Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…As Collins, Knotts, and Schiff (2012) have illustrated, this can be accomplished in many ways. They present 11 ideas, including adding to the curriculum required internship and career preparation courses and embedding elements of career preparation in other courses.…”
Section: Discussion: Enhancing Workplace Relevancementioning
confidence: 99%
“…A second strategy, which might be called “resisting the flow,” involves placing greater emphasis in academic programs on the development of skills that respondents did not associate with formal education. As Collins, Knotts, and Schiff (2012) have illustrated, this can be accomplished in many ways. They present 11 ideas, including adding to the curriculum required internship and career preparation courses and embedding elements of career preparation in other courses.…”
Section: Discussion: Enhancing Workplace Relevancementioning
confidence: 99%
“…In terms of career advising, some faculty advisors have created innovative approaches to help students think about life after college. For example, some departments offer courses to help students with career-oriented advising in a range of disciplines, including geography (Munski, 1983) and political science (Collins, Knotts, & Schiff, 2012). Nevertheless, the practical steps necessary to apply to a professional school may involve issues not typically covered by a traditional faculty or primary-role advisor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After all, that is how legacies are created, and there is a natural expectation that protégés will follow their mentors’ paths. However, Collins, Knotts, and Schiff (2012) found that PhD-granting departments offer less career preparation than BA or MA departments. Everyone must adapt to the new realities, including tenured faculty who never had to deal with the stresses that contingent faculty encounter and who may have little experience in the nonacademic world.…”
mentioning
confidence: 99%